INFLUENCE OF PRE-MARITAL COUNSELLING ON SUSTAINABILITY OF MARRIAGES IN GREATER ACCRA REGION, GHANA: PRE-MARITAL COUNSELLING ON SUSTAINABILITY OF MARRIAGES - Kissi-Abrokwah, Bernard; Aboyom Anontise, Isaac (Advances in Social Sciences Research Journal, 2021)
The study focused on elements discussed during pre-marital counselling and how those elements mediate on the sustainability of marriages in Greater Accra Region. Concurrent triangulation mixed method design was chosen for the study. For the quantitative phase 100 marriage people were randomly selected from 10 churches. At the qualitative phase 4 head pastors were conveniently selected from the 10 churches. Mean and standard deviation was used to analysed the questionnaire for the quantitative phase while the semi-structured interview scheduled was thematically analysed to explain issues as they emerged in the study. The study showed conflict resolution, communication, adjusting to individual difference, sex and romance, family lifecycles in marriage and separation from past-memories and families were some elements discussed during pre-marital counselling to help sustain the marriages. Again, respondents were of the view that pre-marital counselling is vital for the sustainability of marriages and should be made compulsory for new couples. Lastly, it was revealed the philosophy of pre-marital counselling is not only being aware of potential land mines in their relationship, but to equip married people to learn the skills necessary to successfully deal with challenges throughout their marriage which help in the sustainability. Therefore, it was recommended that the churches should employ professional counsellors who understand the principle of marriage counselling to perform the act of counselling and follow-up service should be done to check if the elements discussed during pre-marital counselling are being put into practice.